UPAYA PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA PERDAGANGAN ORANG - Nelsa Fadilla (Jurnal Hukum dan Peradilan, 2016)
The data findings by the Indonesia Child Protection Commission (KPAI) reported that child trafficking tends to increase during the period of 2010 to 2012. In 2010 there were 410 cases, in 2011 there were 480 cases and in 2012 the case increased again up to 673 cases. The increasing cases of child trafficking have become a serious concern in the attempt of human trafficking eradication, especially children. The business not only in the form of law enforcement, preventively, repressively, and responsively but also related to the restoration or protection of children who become the victims of human trafficking (child trafficking) even after the completion of criminal proceedings with a view of restoring the child future.Keywords : legal protection , children , human trafficking.